(untitled) (Journal of Food and Dietetics Research, 2024)
Consumption of low iron bioavailability foods is the main contributing factor of iron deficiency for young children, a major public health problem especially common in our low income African countries. This study aimed at utilizing traditional foodstuffs to develop nutrient dense and iron bioavailability complementary foods in eastern D.R. Congo. Nutrient and anti-nutrient content were carried out using appropriate methods. The complementary foods were formulated by extrusion cooking and ground into flour that could be reconstituted into porridge for child feeding as recommended by Codex alimentarius. In-vitro iron availability was measured as Fe (II) bioavailability obtained by a method combining in-vitro protein digestion and dialysis (IVPD-dialysis). Phytic acid content was done by HPLC analysis method of phytic acid with modifications. The foods were formulated to meet the Recommended Dietary Allowance (RDA) for 6 month olds. Three (3) formulated complementary foods (CF0221, CF0322 and CF0423) composed of four (4) selected traditional foodstuffs: non-germinated amaranth grain (Amaranthus cruentus), maize (Zea mays), termites (Macrotermes subhylanus) and dagaa fish (Rastreneobola argentea) result in this investigation. Complementary foods developed and precooked products obtained contained 914.5-1234.0 mg/100g phytic acid and <5% bioavailability of non-heme iron. Phytate/iron molar ratio was beyond the critical limits for all the foods. The foods contained up to 3.3% bioavailable iron after pepsin digestion and up to 2.5% bioavailable iron after pepsin + pancreatin digestion. This study provides evidence that eastern D.R. Congo has traditional foodstuffs which are nutrient dense and iron bioavailability content. Traditional grains studied have anti-nutrients and reducing them is necessary before processing to complementary foods. Germinating amaranth grain may reduce phytic acid further improving mineral bioavailability. Termite and dagaa fish can be utilized in processing nutrient dense and acceptable complementary foods. It is therefore recommended that both traditional animal and plant foods be exploited. Facilitation to commercialize and patent the process and products should be done to enable full exploitation.